Celiac disease diagnosis: simple rules are better than complicated algorithms - Catassi, Carlo; Fasano, Alessio (The American journal of medicine, 2010)
Celiac disease is the only treatable autoimmune disease, provided that a correct diagnosis is achieved and a strict, lifelong gluten-free diet is implemented. The current diagnostic algorithm for celiac disease includes initial screening serological tests, followed by a confirmatory small intestinal biopsy showing the autoimmune insult typical of celiac disease. The biopsy, considered the diagnostic gold standard, has been recently questioned as a reliable and conclusive test for every case. Indeed, the wide variability of celiac disease-related findings suggests that it is difficult to conceptualize the diagnostic process into rigid algorithms that do not always cover the clinical complexity of this disease. Instead we find clinically useful the shifting to a quantitative approach that can be defined as the "4 out of 5" rule: the diagnosis of celiac disease is confirmed if at least 4 of the following 5 criteria are satisfied: typical symptoms of celiac disease; positivity of serum celiac disease immunoglobulin, A class autoantibodies at high titer; human leukocyte antigen (HLA)-DQ2 or DQ8 genotypes; celiac enteropathy at the small bowel biopsy; and response to the gluten-free diet.